All my mother's lovers : a novel - Masad, Ilana (Dutton, an imprint of Penguin Random House LLC, 2020)
"Intimacy has always eluded twenty-seven-year-old Maggie Krause - despite being brought up by married parents, models of domestic bliss - until, that is, Lucia came into her life. But when Maggie's mom, Iris, dies in a car crash, Maggie returns home only to discover a withdrawn dad, an angry brother, and, along with Iris's will, five sealed envelopes, each addressed to a mysterious man she's never heard of. In an effort to run from her own grief and discover the truth about Iris - who made no secret of her discomfort with her daughter's sexuality - Maggie embarks on a road trip, determined to hand-deliver the letters and find out what these men meant to her mother. Maggie quickly discovers Iris's second, hidden life, which shatters everything Maggie thought she knew about her parents' perfect relationship. What is she supposed to tell her father and brother? And how can she deal with her own relationship when her whole world is in freefall?" --Amazon.com.